Organic Versus Conventional – a Comparative Study on Quality and Nutritive Value of Selected Vegetable Crops of Southern India (SAARC Journal of Agriculture, 2020)
Vegetables are defined as edible plant parts generally consumed raw or cooked with a main dish, in a mixed dish, as an appetizer or as a salad. Food safety aspects related to microbial quality (total plate count, yeast and mold and food borne pathogens) and toxic residue (heavy metals) and mineral content were investigated for vegetables such as green leafy vegetable, salad vegetables, sprouts, brinjal, green chilies and French beans collected from organic and conventional outlets from Mysore region, Karnataka, India. Microbial analysis was carried out using standard procedures and mminerals (Ca, K, Fe, Cu, Mg, Mn and Zn) and heavy metals (Cd and Pb) were determined. Significant variations (p>0.05) were observed for microbial quality among organic and conventional vegetables. Mineral and vitamin C content were also significantly higher (p>0.01) in organic samples. Heavy metal contamination for lead and cadmium tested positive for conventional samples while organic samples tested negative. The variables that contributed most for the variability were heavy metal contamination, mineral and vitamin C content. Organically grown vegetables were free from heavy metals and safe for consumption, as well as they are rich in mineral and vitamin C content in comparison to conventional samples.SAARC J. Agri., 18(1): 99-116 (2020)